Assessment of Lecturer Work Effectiveness: Mediating Organizational Citizen Behavior Based on Organizational Commitment and Work Motivation - Aspan, Henry; Rosli, Rozaini; Prabowo, Ari; Wahyuni, Etty Sri (Journal of Ecohumanism, 2025)
Lecturers’ work effectiveness has a very important role in the current era because it is directly related to the quality of higher education which is one of the keys to successful human resource development. This study seeks to uncover the complex mechanisms underlying the relationship between organizational commitment, work motivation, organizational citizenship behavior (OCB) and lecturers’ work effectiveness, and lecturer work effectiveness. This type of research is associative research. The types of data used are primary data and secondary data obtained from interview questionnaires and documentation studies. Population The population in this study are all lecturers at Private Universities in Medan City based on PD-Dikti data there are 23 Universities. The sample withdrawal used is saturated sampling. So that the number of samples is directly determined as many as 120 respondents by taking 5 lecturers or respondents randomly in each university. Data analysis was carried out using structural equation modeling (SEM) techniques with Smart-PLS analysis tools to test the direct and indirect relationships between these variables. The results explain that work motivation directly has a positive and significant effect on work effectiveness, organizational commitment directly has no positive and insignificant effect on work effectiveness, work motivation directly has a positive and significant effect on organizational citizenship behavior, organizational commitment directly has a positive and significant effect on organizational citizenship behavior, organizational citizenship behavior directly has a positive and significant effect on work effectiveness, work motivation indirectly has a significant effect on work effectiveness through organizational citizen behavior, and organizational commitment indirectly has no significant effect on work effectiveness through organizational citizen behavior.